Instruction and Inspiration: Fifteenth-Century Codicological Recipes. (2nd January 2018) - Griffin, Carrie
Abstract: English codicological recipes survive in great numbers in manuscripts that were produced in the later Middle Ages. I argue that they suggest a little-theorized engagement with the medieval manuscript. Such recipes are not simply and straightforwardly instructional: in fact, they offer us fascinating glimpses into late-medieval perspectives on that relationship between the written word and the decorative aspects of words on a page, a nexus that seems central to the medieval book and that must have been a central cultural and visual symbol. Moreover, they also show that manuscript and document production was increasingly less specialized and occurring in domestic contexts in the fifteenth century. This article will be twofold, looking first at the landscape of surviving recipes, and examining in a more speculative way the relationship between their content, their materiality, and their imaginative qualities.